1. we need to find g(3) and g'(3) to write point slope form of the tangent line
g(3)=cos(f(3))=[tex]cos(\frac{5 \pi}{3})=\frac{1}{2}[/tex]
now to find g'(3)
use chain rule
[tex]g'(x)=\frac{d}{dx}cos(f(x))=-sin(f(x))*f'(x)[/tex] so
[tex]g'(3)=-sin(f(3))*f'(3)=-sin(\frac{5 \pi}{3})*\sqrt{3}=[/tex] [tex](\frac{\sqrt{3}}{2})(\sqrt{3})=\frac{3}{2}[/tex]
the equation of a line that passes through (x1,y1) and having a slope of m is
[tex]y-y_1=m(x-x_1)[/tex]
we know it passes through (3,1/2) and has a slope of 3/2
so the equation of the tangent line at x=3 is
[tex]y-\frac{1}{2}=\frac{3}{2}(x-3)[/tex]
2.ah, difference quotient
[tex]\lim_{x \to \frac{\pi}{4}} \frac{f(x)-f(\frac{\pi}{4})}{x-\frac{\pi}{4}}=[/tex]
[tex]\lim_{x \to \frac{\pi}{4}} \frac{\sqrt{tan(2x+\frac{3 \pi}{4})}-\sqrt{tan(2(\frac{\pi}{4})+\frac{3 \pi}{4})}}{x-\frac{\pi}{4}}=[/tex]
[tex]\lim_{x \to \frac{\pi}{4}} \frac{\sqrt{tan(2x+\frac{3 \pi}{4})}-1}{x-\frac{\pi}{4}}=[/tex]
I don't know how to simplify further